Technology of Harmonious Organization of Psychological and Physical Training of Students-Wrestlers - Erimbetov Bayrambay Karlibaevich (Periodica Journal, 2022)
This article deals with the organization of psychological and physical training of student wrestlers. Proposals and recommendations on the harmonious organization of psychological and physical training have also been developed
Keywords: student; wrestling; technique; psychological